Assessment of the Pollution Load of Effluents Discharged from Higher Institutions in Ethiopia: The Case of Bahir Dar University Zenzelma Campus - Mekuanint Lewoyehu; Nibret Abeje; Solomon Addisu (International Journal of Analytical Chemistry)
Waste from industries, universities, and other institutions makes water a scarce resource. Although higher institutions have an honorable and principled responsibility to the environment, most higher institutions are not performing sensibly; they discharge untreated solid and liquid wastes into the environment. The objective of this study was, thus, to assess the pollution load of effluents from Bahir Dar University Zenzelma campus, Ethiopia. Wastewater samples were collected and analyzed for physicochemical and biological qualities and heavy metal levels. The phosphate (17.2–216.17 mg/L), BOD5 (51–86 mg/L), ammonia (0.02–10.29 mg/L), turbidity (22–580 NTU), total suspended solids (230–1293.33 mg/L), electrical conductivity (241–1492.03 μS/cm), and total hardness (111.67–490 mg/L) levels surpassed the wastewater discharge limit stated by WHO, environmental protection authority, Compulsory Ethiopian Standard, and Environmental Health and Safety guidelines and did not fit wastewater reuse standard for irrigation and livestock drinking. 100% of the samples were not fit for livestock drinking as the coliform bacterium count exceeded the threshold level. Copper (0.006–1.75 mg/L), lead (0.019–0.18 mg/L), and cadmium (0.007–0.196 mg/L) levels crossed the wastewater discharge limit and were not fit for irrigation and livestock drinking, while the level of manganese (nill–0.01 mg/L) was under the threshold limit. Values of the water quality parameters were higher on the downstream site than at the upstream site showing the pollution load of Zenzelma campus effluents on the local environment (Ch’imbil River); wastewater used for irrigation and livestock drinking is unsafe. Thus, it requires immediate waste management interventions and appropriate waste treatment before being released into the environment.